2021
DOI: 10.3390/pathogens10111446
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro 3D Staphylococcus aureus Abscess Communities Induce Bone Marrow Cells to Expand into Myeloid-Derived Suppressor Cells

Abstract: Staphylococcus aureus is the main causative pathogen of subcutaneous, bone, and implant-related infections, forming structures known as staphylococcal abscess communities (SACs) within tissues that also contain immunosuppressive myeloid-derived suppressor cells (MDSCs). Although both SACs and MDSCs are present in chronic S. aureus infections, it remains unknown whether SACs directly trigger MDSC expansion. To investigate this, a previously developed 3D in vitro SAC model was co-cultured with murine and human b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…At the end of demonstrating that BCA kills MRSA within OLCN of infected bone via TEM assessment of necrotic bacteria morphology, we interrogated TEM phenotypes of S. aureus within in vitro biofilm, as previously described (Hofstee et al, 2021). By TEM imaging of SACs grown in a collagen hydrogel (Figures 4A-C (low magnification), Figures 4D-F (high magnification)), we confirmed the phenotype of vital S. aureus in vitro.…”
Section: Bca Effects On Mrsa Within Olcnsupporting
confidence: 53%
“…At the end of demonstrating that BCA kills MRSA within OLCN of infected bone via TEM assessment of necrotic bacteria morphology, we interrogated TEM phenotypes of S. aureus within in vitro biofilm, as previously described (Hofstee et al, 2021). By TEM imaging of SACs grown in a collagen hydrogel (Figures 4A-C (low magnification), Figures 4D-F (high magnification)), we confirmed the phenotype of vital S. aureus in vitro.…”
Section: Bca Effects On Mrsa Within Olcnsupporting
confidence: 53%
“…As an example, our laboratory studies granulocytic myeloid‐derived suppressor cells (G‐MDSCs), a developmentally stunted PMN‐like population with significant immunosuppressive properties. First described in the context of cancer, 118 we have identified a detrimental role for G‐MDSCs in promoting S. aureus prosthetic joint infection. 119 G‐MDSC infiltrates are also present during S. aureus craniotomy infection and inhibit PMN killing of S. aureus .…”
Section: Discussionmentioning
confidence: 88%
“…13 As of 2017, four HDAC inhibitors were approved for use by the United States properties. First described in the context of cancer, 118 we have identified a detrimental role for G-MDSCs in promoting S. aureus prosthetic joint infection. 119 G-MDSC infiltrates are also present during S. aureus craniotomy infection and inhibit PMN killing of S. aureus.…”
Section: Translational Epigeneticsmentioning
confidence: 87%
“…Chronic and prolonged infections with S. aureus represent the highest burden of disease, with decreasing likelihood of treatment success as the infection becomes established [ 23 ]. In this Special Issue, two different publications [ 24 , 25 ] showed the potential of 3D models in gaining more insight towards controlling the burden caused by such a threatening pathogen. Hofstee et al [ 24 ] showed that staphylococcal abscess communities cause myeloid-derived suppressor cell (MDSC) expansion from bone marrow cells and identified possible mediators to be targeted as an additional strategy for treating chronic S. aureus infections.…”
mentioning
confidence: 99%
“…In this Special Issue, two different publications [ 24 , 25 ] showed the potential of 3D models in gaining more insight towards controlling the burden caused by such a threatening pathogen. Hofstee et al [ 24 ] showed that staphylococcal abscess communities cause myeloid-derived suppressor cell (MDSC) expansion from bone marrow cells and identified possible mediators to be targeted as an additional strategy for treating chronic S. aureus infections. Parente et al [ 25 ] developed a 3D model of osteomyelitis (OM), a bone condition primarily induced by S. aureus infections, based on co-cultures of S. aureus and murine osteoblastic MC3T3-E1 cells on magnesium-doped hydroxyapatite/collagen I (MgHA/Col) scaffolds that closely recapitulate the bone extracellular matrix.…”
mentioning
confidence: 99%